2016
DOI: 10.1016/j.myc.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Barcoding sequences clearly separate Chroogomphus mediterraneus (Gomphidiaceae, Boletales) from C. rutilus, and allied species

Abstract: Chroogomphus mediterraneus, a species described from the Balearic Islands, is confirmed as belonging to the genus Chroogomphus, instead of the genus Gomphidius, as it appears in taxonomic databases. Chroogomphus mediterraneus shows macroscopic features similar to Chroogomphus fulmineus and C. rutilus, species with which it has been confused in the literature. However, analyses based on comparison of barcoding sequences (internal transcribed spacers of nuclear ribosomal DNA), and a review of the morphological f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 23 publications
(19 reference statements)
2
19
0
Order By: Relevance
“…The genus can be found throughout the Northern Hemisphere with the exception of only one species, C. papillatus, which was reported from the Southern Hemisphere by Raithelhuber (1974). There is morphological and molecular evidence of intercontinental distribution for C. purpurascens and C. rutilus, which both occur in Europe and Asia (Miller and Aime 2001;Li et al 2009;Martín et al 2016;Scambler et al 2018). Our phylogenetic tree, obtained from ML and BI analyses (Figure 1), is in accordance with Scambler et al (2018), with the division of the genus into the subgenera Chroogomphus, Floccigomphus and Siccigomphus.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…The genus can be found throughout the Northern Hemisphere with the exception of only one species, C. papillatus, which was reported from the Southern Hemisphere by Raithelhuber (1974). There is morphological and molecular evidence of intercontinental distribution for C. purpurascens and C. rutilus, which both occur in Europe and Asia (Miller and Aime 2001;Li et al 2009;Martín et al 2016;Scambler et al 2018). Our phylogenetic tree, obtained from ML and BI analyses (Figure 1), is in accordance with Scambler et al (2018), with the division of the genus into the subgenera Chroogomphus, Floccigomphus and Siccigomphus.…”
Section: Discussionsupporting
confidence: 72%
“…We constructed an ITS dataset of our newly generated sequences along with closely related sequences that were downloaded from GenBank (Li et al 2009;Martín et al 2016;Scambler et al 2018). We included species of Gomphidius Fr.…”
Section: Sequence Alignment and Phylogenetic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Nithaniyal and Parani (2016) used rbcL, matK, internal transcribed spacer 2 (ITS2) and trnH-psbA markers for identification of Terminalia spp. Martin et al (2016) reported that DNA barcoding of ITS in the nuclear ribosomal DNA (nrDNA) region supported the separation of Chroogomphus mediterraneus from C. rutilus. In Mezzasalma et al's (2017) study, four barcode loci -rbcL, matK, trnH-psbA and ITS -were used to identify the traditional medicine species Cyperus articulatus within the natural flora of the Amazon.…”
Section: Introductionmentioning
confidence: 99%